Biomechanics of the lead straight punch of different level boxers - Liu, Yang; Zhu, Zhiqiang; Chen, Xiuxiu; Deng, Chengyuan; Ma, Xiujie; Zhao, Bin (Frontiers in Physiology, 2022)
We analyze and compare the differences in the biomechanical parameters between the lead straight punch and the index of force development of the lower extremities of boxers of different levels of ability. This can bridge the technical gap and provide insight and information for training strategies and athlete selection. To this end, a synchronized Vicon infrared 3D motion-capture system, two Kistler force platforms, and Kistler 8 target sensors were used for analysis. Sixteen boxers were recruited and sorted into an elite group (height 181.14 ± 3.01 cm, body mass 76.00 ± 10.028 kg) and a junior group (179.67 ± 5.84 cm, body mass 75.47 ± 12.19 kg), and their lead straight punch was then compared and analyzed. Three punch velocity indexes—peak velocity, contact velocity and Punching deceleration rate—six strength indexes—impulse, peak force, relative strength, peak time (frame), rate of force development (RFD), and movement time—and five exertion of both legs indexes— peak force, peak force/body mass, peak time, RFD index, and RFD/body mass index—were selected for analysis. Significant differences in the peak punch velocity and contact velocity were found between the two groups (7.162 ± 0.475 m•s−1vs. 6.317 ± 0.415 m•s−1, Cohen’s d = 1.89, p < 0.01, 5.557 ± 0.606 m•s−1 vs. 4.874 ± 0.385 m•s−1, Cohen’s d = 1.34, p < 0.05). Furthermore, significant differences were noted in the peak force [(1507.99 ± 411) N vs. (1035.45 ± 220) N, Cohen’s d = 1.43, p < 0.01], relative strength [(21.04 ± 5.88) N•kg−1 vs. (15.61 ± 2.53) N•kg−1, Cohen’s d = 1.19, p < 0.05], impulse [(88.61 ± 25.88) N•ms−1 and (60.53 ± 9.03) N•ms−1, Cohen’s d = 1.45, p < 0.05], and RFD [(88.61 ± 25.88) N•ms−1 and (60.53 ± 9.03) N•ms−1, Cohen’s d = 1.45, p < 0.05]. Among the four indexes of the lower extremities from two embedded Kistler force platforms, there were significant differences in the lead leg’s peak force/body mass [(19.68 ± 4.096) N•kg−1vs. (13.320 ± 2.223) N•kg−1, t = 3.902, Cohen’s d = 1.92, p < 0.01], RFD index [(16.90 ± 3.269) N•ms−1vs. (10.28 ± 4.313) N•ms−1, Cohen’s d = 1.72, p < 0.01], and RFD/body mass index [(23.47 ± 4.09%) N•ms−1Kg−1 vs. (15.38 ± 5.65%) N•ms−1Kg−1, Cohen’s d = 1.64, p < 0.01]. There were no significant differences in the four indexes on the rear leg between the two groups (p > 0.05). Based on the disparity in the effect of the lead straight punch and the biomechanical parameters of both lower extremities, the boxers must attach importance to sequential acceleration-braking training to improve the terminal velocity of the hand, and thus improve the contact velocity. Furthermore, it is advised that coaches and practitioners carefully consider increasing start-up strength training of the lead leg and attempt to improve the peak velocity of the lead straight punch. In addition, these biomechanical parameters can be used as criteria for the selection of boxers.